VLS-grown diffusion doped ZnO nanowires and their luminescence properties. (17th July 2015) - Roy, Pushan Guha; Dutta, Amartya; Das, Arpita; Sen, Sayantani; Pramanik, Pallabi; Bhattacharyya, Anirban
Abstract: Zinc Oxide (ZnO) nanowires were deposited by vapor–liquid–solid (VLS) method on to aluminum doped ZnO (AZO) thin films grown by sol-gel technique. For various device applications, current injection into such nanowires is critical. This is expected to be more efficient for ZnO nanowires deposited on to AZO compared to those deposited on to a foreign substrate such as silicon. In this work we compare the morphological and optical properties of nanowires grown on AZO with those grown under similar conditions on silicon (Si) wafers. For nanowires grown on silicon, diameters around 44 nm with heights around 2.2 μ m were obtained. For the growth on to AZO, the diameters were around 90 nm while the heights were around 520 nm. Room temperature photoluminescence (RT-PL) measurements show improved near band-edge emission for nanowires grown on to AZO, indicating higher material quality. This is further established by low temperature photoluminescence (LT-PL) measurements where excitonic transitions with width as small as 14 meV have been obtained at 4 K for such structures. Electron energy loss spectroscopy (EELS) studies indicate the presence of Al in the nanowires, indicating a new technique for introduction of dopants into these structures. These results indicate that ZnO nanowires on sol-gel grown AZO thin films show promise in the development of various optoelectronic devices.